Comparative Analysis of En-Bloc and Conventional Transurethral Resection of Bladder Tumor (TURBT) for Non-Muscle Invasive Bladder Cancer: A Systematic Review and Meta-Analysis - Reynaldo, Reynaldo; Monoarfa, Richard Arie; Duha, Diki Arma (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
In order to treat non-muscle invasive bladder cancer, this study will compare and contrast conventional transurethral resection of bladder tumors (TURBT) with En-bloc resection (ERBT). It will also assess the efficacy, safety, and recurrence rates of these two methods. We searched PubMed and Sience Direct for relevant articles published between 2013 and 2023. Articles from randomized controlled trials, retrospective analyses, and prospective studies comparing non-muscle invasive bladder cancer therapies employing en bloc versus conventional TURBT are included in this analysis. Measuring effect size was done using Mean Difference (MD) and Odd Ratio (OR) with 95% CI. There is statistical significance when the p-value is less than 0.05. Fourteen studies were eligible for inclusion. With fewer tumor recurrences (OR 0.66; 95% [CI]  0.52, 0.84; I2 = 6%; P = 0.0007), ERBT proved to be superior to TURBT. There was a decrease in the occurrence of perioperative complications and outcomes associated with ERBT, including bladder perforation and obturator nerve injury.  According to the fourteen articles that were included, patients receiving ERBT experienced much fewer complications, recurrences, hospital stays, and catheterization time than those receiving conventional TURBT.